2018
DOI: 10.1371/journal.pone.0195353
|View full text |Cite
|
Sign up to set email alerts
|

Crayfish plague in Japan: A real threat to the endemic Cambaroides japonicus

Abstract: Global introductions of aquatic species and their associated pathogens are threatening worldwide biodiversity. The introduction of two North American crayfish species, Procambarus clarkii and Pacifastacus leniusculus, into Japan in 1927 seems to have negatively affected native Japanese crayfish populations of Cambaroides japonicus. Several studies have shown the decline of these native populations due to competition, predation and habitat colonization by the two invasive North American crayfish species. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…this is the first report of this disease in Indonesia, which is the second country in Asia (after Japan; Mrugała et al, 2017;Martín-Torrijos et al, 2018) where established populations of North American invasive crayfish have been confirmed to carry this pathogen. The spread of the disease along with escaping crayfish, and possibly also with waste water from aquaria or ponds, is probable.…”
Section: Discussionmentioning
confidence: 78%
“…this is the first report of this disease in Indonesia, which is the second country in Asia (after Japan; Mrugała et al, 2017;Martín-Torrijos et al, 2018) where established populations of North American invasive crayfish have been confirmed to carry this pathogen. The spread of the disease along with escaping crayfish, and possibly also with waste water from aquaria or ponds, is probable.…”
Section: Discussionmentioning
confidence: 78%
“…Schrimpf et al (2014) confirmed that this species can serve as a vector for the crayfish plague pathogen Aphanomyces astaci, which could pose a threat to native Japanese freshwater species. For instance, Martín-Torrijos et al (2018) reported that the pathogen A. astaci caused two mass mortality events in the endangered Japanese native crayfish Cambaroides japonicus. In addition, invasive E. sinensis and native E. japonica have the same numbers of chromosomes (2n = 146) (Lee et al, 2004); therefore, it is possible that the two species could hybridize and produce viable offspring.…”
Section: Further Perspectivesmentioning
confidence: 99%
“…Thus, the current knowledge regarding A. astaci diversity is based on research with pathogen strains that have been mainly isolated from infected European crayfish or North American crayfish stocked into European freshwaters. A recent exception to this is a study by Panteleit et al (2019), demonstrating that the North American crayfish Faxonius rusticus (Girard, 1852) carries a novel genotype of A. astaci, as well as the recent detections of the pathogen in invasive North American crayfish in Japan (Mrugała et al, 2017;Martín-Torrijos et al, 2018), Indonesia (Putra et al, 2018) and South America (Peiró et al, 2016). Currently, there are no reports of A. astaci causing epidemics, disease or population collapses among native hosts on North American continent (OIE, 2019), although several different North American crayfish species do act as permanent reservoirs of A. astaci outside their original distribution range (Aquiloni et al, 2011;Kozubíková et al, 2011;Filipová et al, 2013;Tilmans et al, 2014;Peiró et al, 2016;James et al, 2017;Kaldre et al, 2017) as well as in captivity (Mrugała et al, 2015;Panteleit et al, 2017).…”
Section: Introductionmentioning
confidence: 99%